The Influence of Perceived Benefits and Ease of Use on Artificial Intelligence Adoption in Accounting - Ayi Astuti; Tamy Ali Januarty; Salma Rahmasari (Penerbit Jurnal Indonesia, 2026)
This study examines the influence of perceived benefits and perceived ease of use on the adoption of Artificial Intelligence (AI) in accounting practice in Indonesia. Using a quantitative approach with a causal design based on the Technology Acceptance Model (TAM) framework, this research involved 240 respondents, accounting practitioners who are members of the Indonesian Institute of Accountants (IAI), selected through random sampling techniques. Data was collected through questionnaires using a five-point Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with Smart PLS software. The results indicate that perceived benefits have a positive and significant effect on AI adoption in accounting practice. Similarly, perceived ease of use also has a significant positive impact on AI adoption. These findings suggest that AI adoption is influenced by the perceived practical benefits and ease of use. Therefore, increasing AI adoption should focus on strengthening practical benefits and simplifying systems to meet the needs of accounting practitioners.